2018
DOI: 10.1007/s10549-018-4793-z
|View full text |Cite
|
Sign up to set email alerts
|

Lnc RNA H19 is associated with poor prognosis in breast cancer patients and promotes cancer stemness

Abstract: This study indicated that H19 was associated with stem cell phenotype in ALDH1-positive breast cancer. H19 regulates CSC and is associated with poor prognosis in breast cancer patients, particularly in triple-negative subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 38 publications
4
66
0
Order By: Relevance
“…However, studies have confirmed that H19 is associated with the stem cell phenotype of aldehyde dehydrogenase 1 (ALDH1)‐positive breast cancer. H19 can affect breast cancer stem cells and lead to poor prognosis in patients with breast cancer . Therefore, we knocked out H19 from resistant CC cells; this action may lead to changes in the characteristics of CC stem cells and in turn result in increased apoptosis under the action of chemotherapeutic drugs and diminished ability to proliferate, migrate, and invade.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have confirmed that H19 is associated with the stem cell phenotype of aldehyde dehydrogenase 1 (ALDH1)‐positive breast cancer. H19 can affect breast cancer stem cells and lead to poor prognosis in patients with breast cancer . Therefore, we knocked out H19 from resistant CC cells; this action may lead to changes in the characteristics of CC stem cells and in turn result in increased apoptosis under the action of chemotherapeutic drugs and diminished ability to proliferate, migrate, and invade.…”
Section: Discussionmentioning
confidence: 99%
“…Another developmentally important lncRNA, H19, promotes cancer progression in several cancers including breast [52,[86][87][88] and is enriched in the ALDH high breast CSC populations of TNBCs [63]. H19 sponges miRNA tumor suppressor, let-7, facilitating a concomitant increase in the breast CSC-enriched pluripotency factor LIN28.…”
Section: H19mentioning
confidence: 99%
“…The long non-coding RNA (lncRNA) H19 can function either as a tumor promoter or as a tumor suppressor, depending on the type of cancer, development stage, or molecular background [8][9][10][11]. The H19 was upregulated in many tumors including esophageal squamous cell carcinoma [12], lung cancer [13], gastric cancer [14], and breast cancer [15], and H19 overexpression contributes to poor prognosis in these patients. However, in osteosarcoma [16] and renal cell carcinoma [17], H19 overexpression contributes to a good prognosis.…”
Section: Introductionmentioning
confidence: 99%